2011
DOI: 10.3928/01477447-20110826-22
|View full text |Cite
|
Sign up to set email alerts
|

Periosteal Avulsion of the Posterolateral Corner of the Knee in an Adolescent: An Unreported Case

Abstract: Isolated injuries of the posterolateral corner of the knee are uncommon injuries in adults and are relatively unheard of in the pediatric population. This article reports a case of a 13-year-old boy who sustained an external rotation injury to his proximal tibia on a slightly flexed knee while playing football. Radiographs showed an avulsed fragment from the lateral femoral condyle. A magnetic resonance image was read as an avulsion of the femoral insertion of the lateral collateral ligament with associated bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Most reports have been of isolated injury to the popliteus tendon, 8 while others report avulsion of both the LCL and popliteus. 3 The characteristic findings are an adolescent athlete with a history of varus-directed force, hemarthrosis, and osteochondral fragment of the distal lateral extra-articular femoral epiphysis visible on radiographs with associated injury to the popliteus and/or LCL on magnetic resonance imaging. 3 , 4 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Most reports have been of isolated injury to the popliteus tendon, 8 while others report avulsion of both the LCL and popliteus. 3 The characteristic findings are an adolescent athlete with a history of varus-directed force, hemarthrosis, and osteochondral fragment of the distal lateral extra-articular femoral epiphysis visible on radiographs with associated injury to the popliteus and/or LCL on magnetic resonance imaging. 3 , 4 …”
Section: Discussionmentioning
confidence: 99%
“… 1 Methods of operative fixation vary from suture repair over a bony bridge, suture repair with suture anchors, and repair with screws and washers. 3 , 8 , 9 , 10 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, several radiological studies have investigated bone bruises and ACL injuries in pediatric patients. 20 , 21 , 23 Bordoni et al 3 reported a higher prevalence and similar distribution pattern of bone bruises and cartilage and meniscal lesions in pediatric patients with ACL injuries compared with adults. However, the distribution pattern was summarized as the location of bone bruises in all included patients instead of classifying the location of the bone bruise in each patient.…”
mentioning
confidence: 93%